2022
DOI: 10.1093/asj/sjac122
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Facial Fat Grafting to Increase Volume Retention: A Systematic Review

Abstract: Background For decades, facial fat grafting is used in clinical practice for volume restoration. The main challenge of this technique is the variable volume retention. Over the past years, studies reported the addition of supplements to augment the fat graft to increase volume retention. Objectives The aim of this systematic review was to investigate which supplements increase volume retention in facial fat grafting as assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 106 publications
0
13
0
Order By: Relevance
“…There are three main purposes of facial fat grafting: volume restoration (filling to the deep layer, providing tissue support, and improving facial contours), fine contouring (filling to the superficial layer, providing limited volumization, and modest regeneration), and tissue repair (intradermal filling, predominantly used to fix aged, and damaged tissue). According to the previous reports of the applicability of various fat products, 14 here, we suggested our pyramidal multipletheory (PMT) fat grafting strategy. The fundamental aspect of this strategy was deep layer filling which provided restoration of volume along with a prominent supportive effect.…”
Section: Strategy For Facial Fat Graftingmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three main purposes of facial fat grafting: volume restoration (filling to the deep layer, providing tissue support, and improving facial contours), fine contouring (filling to the superficial layer, providing limited volumization, and modest regeneration), and tissue repair (intradermal filling, predominantly used to fix aged, and damaged tissue). According to the previous reports of the applicability of various fat products, 14 here, we suggested our pyramidal multipletheory (PMT) fat grafting strategy. The fundamental aspect of this strategy was deep layer filling which provided restoration of volume along with a prominent supportive effect.…”
Section: Strategy For Facial Fat Graftingmentioning
confidence: 99%
“…We believe that in the premise of improved proficiency, the outcomes are worth the cost of the moderately increased procedure complexity.Current studies of fat grafting have advanced our understanding of the dynamic progression of grafted fat tissue, postoperative clinical progress, clinical indications, and predictors of outcomes. However, the limitations of study such as restricted sample size, lack of a validated patient-reported outcome measure, clinician outcome measure, and lack of a group for comparison, more evidence are necessary for designating the optimal fat harvesting, processing, techniques, and individual patients best suited to receive fat grafting treatment, and to better define the indications for recipient-site preconditioning and the cellenriched method in the filling field 14. The adoption of a standardized technique would offer potential advantages for future clinical practice and outcome-based research, such as an increase in the possibility of multicenter comparative studies and a reduction in operate-related bias in clinical analyses comparing fat harvesting and processing techniques.…”
mentioning
confidence: 99%
“…19 Despite the variable retention rate, patient satisfaction rates were reported to be greater than 90%. 19 It is noteworthy that the studies in this level IV systematic review were of poor quality with lack of properly standardized protocols for grafting, weak reliability rating, and poor heterogeneity.…”
Section: Facial Fat Graftingmentioning
confidence: 99%
“…The efficacy or retainment of the fat injected can be a frustrating aspect of this procedure with long-term volume retention ranging from 25 to 80%. [19][20][21][22] This procedure is commonly performed in conjunction with facelift, lip lift, and other upper and midface surgical procedures. In lower facial rejuvenation, fat injections can be performed in the lower cheek, nasolabial folds, marionette lines, chin, and lips.…”
Section: Facial Fat Graftingmentioning
confidence: 99%
See 1 more Smart Citation